Premature ejaculation: modern notions - Kocharyan, Garnik (Psychiatry, Neurology and Medical Psychology, 2018)
Data are submitted on the frequency of premature ejaculation and its definitions in the International Classification of Diseases of the 10th Revision, the Diagnostic and Statistical Manual of Mental Disorders of the 4th and 5th Revisions (USA), and in the recommendations of the special committee of the International Society for Sexual Medicine. The biological and the biopsychosocial approach to assessing the duration of sexual intercourse are presented and characterized. It is concluded that the biological approach to its evaluation which is fully applicable to animals is insufficient for humans, since it does not take into account the extremely important recreational aspect of intimate intimacy in people. Psychogenic and biogenic factors involved in the formation of premature ejaculation are presented. It is concluded that attempts to completely eliminate or significantly downplay the role of biogenic factors in the genesis of this dysfunction should be considered untenable.